Assessment of the Effect of Diagonal Reinforcement Quantity on Seismic Behavior of Coupling Beams. Issue 16 (10th December 2022) - Han, Sang Whan; Jang, Jong Seok; Kim, Taeo
ABSTRACT: The aim of this study was to scrutinize the seismic behavior of coupling beams according to the quantity of diagonal reinforcement. Four specimens with different diagonal reinforcement quantities were tested with reversed cyclic loading. The shear strength and deformation capacity of coupling beam specimens were compared to those from ACI 318–19 and ASCE 41–17, respectively. With a decrease in diagonal reinforcement, shear strength and chord rotation capacity of diagonal reinforced coupling beams (DRCBs) diminished. An empirical equation to calculate the minimum quantity of diagonal reinforcement was proposed to satisfy the limiting deformation capacity using regression analyses with test data of 45 collected DRCB specimens.